2016
DOI: 10.1111/nmo.12975
|View full text |Cite
|
Sign up to set email alerts
|

Jackhammer esophagus: Observations on a European cohort

Abstract: The symptom dysphagia is accompanied with strong contractions of the LES, signs of a possible outflow obstruction, and a very high DCI. The presence of a multipeaked contraction seems to be of limited relevance, and caution is warranted in labeling patients with one hypercontractile swallow as normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 24 publications
10
68
0
8
Order By: Relevance
“…A recent publication by Bredenood et al. confirmed that the chest pain in Jackhammer esophagus was not related to the value of DCI, however, dysphagia did show a correlation with DCI and an elevated intrabolus pressure . In our study, the parameters evaluated among the first five intact swallows and the swallow with the maximal DCI revealed higher POSP‐CI‐tc/PREP‐CI‐tc in patients with IDQ ≥ 6 than those ≤6.…”
Section: Discussionsupporting
confidence: 48%
“…A recent publication by Bredenood et al. confirmed that the chest pain in Jackhammer esophagus was not related to the value of DCI, however, dysphagia did show a correlation with DCI and an elevated intrabolus pressure . In our study, the parameters evaluated among the first five intact swallows and the swallow with the maximal DCI revealed higher POSP‐CI‐tc/PREP‐CI‐tc in patients with IDQ ≥ 6 than those ≤6.…”
Section: Discussionsupporting
confidence: 48%
“…Importantly, Herregods et al. first revealed a trend towards an association between dysphagia and the DCI in HRM, that reached a significant level when only hypercontractile swallows were analysed . Moreover, they reported that patients had dysphagia when contractions of the LES zone exceeded 2000 mm Hg/s/cm.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, pathophysiological factors causing this new entity are still a matter of debate. Hypercontractility may be present as primary motility disorder but was also registered in the context of outflow obstruction and gastroesophageal reflux disease (GERD) . Furthermore, researchers emphasized the co‐incidence of symptoms like dysphagia and non‐cardiac chest pain in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…6 Though hypercontractile swallows manifest as single- or multi-peaked contractions, the clinical relevance of these contraction types is unclear. 22 …”
Section: Interpretation Of Esophageal Hrmmentioning
confidence: 99%